2021
DOI: 10.3389/fpls.2021.638969
|View full text |Cite
|
Sign up to set email alerts
|

Genomic Breeding for Diameter Growth and Tolerance to Leptocybe Gall Wasp and Botryosphaeria/Teratosphaeria Fungal Disease Complex in Eucalyptus grandis

Abstract: Eucalyptus grandis is one of the most important species for hardwood plantation forestry around the world. At present, its commercial deployment is in decline because of pests and pathogens such as Leptocybe invasa gall wasp (Lepto), and often co-occurring fungal stem diseases such as Botryosphaeria dothidea and Teratosphaeria zuluensis (BotryoTera). This study analyzed Lepto, BotryoTera, and stem diameter growth in an E. grandis multi-environmental, genetic trial. The study was established in three subtropica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 78 publications
0
7
1
Order By: Relevance
“…The positive (unfavourable) genetic correlation between tree height and the severity of white pine weevil attack represents a challenge for simultaneous genetic improvement for both traits and some trade-off should be implemented. This is in opposite to cases where tree height is positively correlated with disease resistance such as white pine weevil in Norway spruce [56] or Leptocybe gall wasp in Eucalyptus grandis [57]. The discrepancy between results from our study compared to those performed in Norway spruce and Eucalyptus grandis might be caused by the fact that our sample is at the early ontogenetic stage and has not passed any previous disease outbreaks while the other studies were performed at the advanced ontogenetic stage of the sample.…”
Section: Different Resistance Mechanisms Found Between Low Elevation (Rxr) Versus Low With Higher Elevation (Rxs) Crossescontrasting
confidence: 93%
“…The positive (unfavourable) genetic correlation between tree height and the severity of white pine weevil attack represents a challenge for simultaneous genetic improvement for both traits and some trade-off should be implemented. This is in opposite to cases where tree height is positively correlated with disease resistance such as white pine weevil in Norway spruce [56] or Leptocybe gall wasp in Eucalyptus grandis [57]. The discrepancy between results from our study compared to those performed in Norway spruce and Eucalyptus grandis might be caused by the fact that our sample is at the early ontogenetic stage and has not passed any previous disease outbreaks while the other studies were performed at the advanced ontogenetic stage of the sample.…”
Section: Different Resistance Mechanisms Found Between Low Elevation (Rxr) Versus Low With Higher Elevation (Rxs) Crossescontrasting
confidence: 93%
“…Such a weak relationship between disease resistance and productivity is rather uncommon. Recent studies showed that tree height is positively correlated with disease resistance such as white pine weevil in Norway spruce [51] or Leptocybe gall wasp in Eucalyptus grandis [52]. In a differing example, Dungey et al [53], and later Kla ´ps ˇte ˇet al [54], investigated Swiss needle cast in Douglas-fir introduced in New Zealand.…”
Section: Different Resistance Mechanisms Found Between Low Elevation ...mentioning
confidence: 99%
“…The genetic material used in this study consisted of 416 E. grandis trees from 60 half-sib families randomly sampled from 3 different sites, Kwambonambi (Siya Quebeka), Mtunzini, and Nyalazi in KwaZulu Natal, South Africa as shown in Fig. 1 ( Mphahlele et al 2021 ). The E. grandis trials were established in August 2012.…”
Section: Methodsmentioning
confidence: 99%
“…Each tree was thus categorized as either 0, 1, 2, or 3. Environmental and trial design information of the study population, the number of families, phenotyped and genotyped individuals are shown in Table 1 , the study population used is a subset of a population used by Mphahlele et al (2021) . Each family contains 15 individuals (progeny) per trial site, with one of these individuals randomly represented in each of the 15 replications.…”
Section: Methodsmentioning
confidence: 99%